Anti-Nutritional, Antifeedant, Development-Distorting, and Insecticidal Impacts of Three EOs on Box Tree Moth Cydalima perspectalis (Walker Lepidoptera: Crambidae) - Ertürk, Ömer; Ünal, Sabri; Yaman, Mustafa; Özden Keleş, Seray (Kastamonu University, 2025)
Aim of study: Buxus plants are widely affected by the box tree moth, Cydalima perspectalis. This study was carried out to determine the activity levels (anti-nutritional, anti-growth and insecticidal activities) of Tanacetum parthenium, Laurus nobilis and Lavandula officinalis essential oils (EOs) on C. perspectalis larvae. Area of study: The lavender, pyrethrum and Laurel bay plants were collected from the Karaçomak dam Azdavay Derelitekke and İnebolu Evrenye Ayvat in Kastamonu. Material and method: Experiments were conducted to determine the biological effects of T. parthenium, L. nobilis and L. officinalis EOs on the potential influence of spawning preference in boxes. The EOs were applied to Buxus plants to prevent leaf eating by C. perspectalis pests because EOs have generally anti-nutritional, antifeedant, development inhibitive, and insecticidal activities. Main results: EOs of T. parthenium, L. nobilis, L. officinalis indicated the greatest decrease in the Relative Growth Rate (RGR) of C. perspectalis pest in different treatment concentrations (%100, %50 and %25 mg/l). This study indicated that RGR reduced with the enhancement of the concentration of the tested oils. Research highlights: T. parthenium, L. nobilis and L. applications of EOs in different concentrations (100%, 50% and 25% mg/l) showed promising results against the Cydalima perspectalis.